-26/3=m+1/3

Simple and best practice solution for -26/3=m+1/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -26/3=m+1/3 equation:


m in (-oo:+oo)

-26/3 = m+1/3 // - m+1/3

-m-26/3-(1/3) = 0

-m-26/3-1/3 = 0

-m-9 = 0 // + 9

-m = 9 // * -1

m = -9

m = -9

See similar equations:

| 3x+ix-2y-8iy=2-4i | | 3(t-4)+7t^2*2t= | | 2(3+j)=28 | | d/3=-6/7 | | n+2/3=5/3 | | 19=w+10 | | b-2/3=4/21 | | m+6=71/11 | | 5(n+3)=95 | | n+(-3)=-8 | | 4(6y-5)=220 | | b/5=-4/7 | | 2(4d-1)=22 | | 43/9=m+4 | | n/-7=4/7 | | x-1/5=29/5 | | x+1/5=51/5 | | 4(b-3)=64 | | 3(c+7)=30 | | 8/9+x=44/9 | | m+2/5=24/35 | | b/7=4 | | k-6/7=8/7 | | 65/6=a-1/6 | | t/-3=5 | | -3/7n=36/7 | | -1/2d=-1/2 | | 1/4b=1/7 | | n+2/7=86/7 | | a-2/3=-2/3 | | -8+n=-65/9 | | -16x^2+96x+256=0 |

Equations solver categories